Comorbid mental disorders with epilepsy in childhood - Y. A. Yakovleva; M. Y. Kissin; E. V. Gumennik; S. V. Semenova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2023)
The clinical and anamnestic method analyzed 496 outpatient records of children and adolescents suffering from epilepsy in order to identify data contributing to the development and influencing the nature and severity of comorbid mental disorder. The presence of cognitive and affective disorders of varying severity was noted in 415 (83.6%) patients. As an addition to the neurological diagnosis was revealed: 171 patients (61.3%) had anxiety-depressive syndrome, 245 patients (87.8%) had emotional-volitional instability syndrome, and 101 patients (36.2%) had autism spectrum disorder (ASD). But further psychiatric verification of these syndromes in accordance with ICD-10 was not carried out. Clinical, neurophysiological and morphological characteristics of comorbid mental symptoms in epilepsy in childhood and adolescence were revealed.